Application of Fluorine in Drug Design During 2010-2015 Years: A Mini-Review - Wang, Bao-Cheng; Wang, Li-Jun; Jiang, Bo; Wang, Shuai-Yu; Wu, Ning; Li, Xiang-Qian; Shi, Da-Yong (Mini Reviews in Medicinal Chemistry, 2017)
Background: The widespread application of fluorine in drug design benefits from distinctive properties. Incorporation of fluorine can positively modulate certain pharmacokinetics properties, including lipophilicity, eletrophilicity, metabolic stability, chemical stability, et al., which were of interest to medicinal chemists. Herein, fluorinated compounds, which have been designed and evaluated for anticancer, antimicrobial, anti-inflammatory and antivirus activity, et al. during the last 6 years (2010-2015) are summarized. Conclusion: The emphasis is to highlight the importance of fluorinated compounds and the changes in the properties of compounds when introducing fluorine atom.
Keywords: drug design